Corporate Social Responsibility in the Digital Age: Navigating Ethical Marketing and Consumer Expectations - Naveed Rafaqat Ahmad (Research Journal of Psychology, 2025)
This study aims to examine the role of Corporate Social Responsibility (CSR) in the digital age, focusing on how ethical marketing practices and consumer expectations shape CSR strategies in modern businesses. The research explores the evolving landscape of CSR in response to digital advancements and how companies navigate the balance between social responsibility and consumer demands. The qualitative method is employed to collect the data through interviews, surveys, and case studies from various industries including textile, food and tech. The findings reveal that businesses integrating ethical marketing practices within their CSR initiatives are more likely to build stronger brand loyalty, enhance consumer trust, and achieve long-term success. Nevertheless, companies that fail to align their digital marketing strategies with genuine CSR efforts risk facing consumer skepticism and damage to their reputation.